2012
DOI: 10.1021/jm300908t
|View full text |Cite
|
Sign up to set email alerts
|

Role of the CAI-1 Fatty Acid Tail in the Vibrio cholerae Quorum Sensing Response

Abstract: Quorum sensing is a mechanism of chemical communication among bacteria that enables collective behaviors. In V. cholerae, the etiological agent of the disease cholera, quorum sensing controls group behaviors including virulence factor production and biofilm formation. The major V. cholerae quorum-sensing system consists of the extracellular signal molecule called CAI-1 and its cognate membrane bound receptor called CqsS. Here, the ligand binding activity of CqsS is probed with structural analogs of the natural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…[21] Ap oint mutation analysiso ft his kinase suggested that CAI-1 was recognized by the fourth to sixth transmembrane a-helix domains of CqsS. [22,23] Similarly,t he first to third transmembrane domains of PhcS might encircle the phc QS signal, causing ac onformation change in its kinase domain. In future studies we intend to investigate the interaction between (R)-3-OH MAME and the ligand-sensing domains of PhcS.…”
Section: Discussionmentioning
confidence: 99%
“…[21] Ap oint mutation analysiso ft his kinase suggested that CAI-1 was recognized by the fourth to sixth transmembrane a-helix domains of CqsS. [22,23] Similarly,t he first to third transmembrane domains of PhcS might encircle the phc QS signal, causing ac onformation change in its kinase domain. In future studies we intend to investigate the interaction between (R)-3-OH MAME and the ligand-sensing domains of PhcS.…”
Section: Discussionmentioning
confidence: 99%
“…The synthetic autoinducers were produced as described previously (25)(26)(27)(28) and were provided as a kind gift by Bonnie L. Bassler and Wai-Leung Ng, (Princeton University, Princeton, NJ and Tufts University, Medford, MA, respectively). The CAI-1 preparation was dissolved in dimethyl sulfoxide to prepare a 5-mM stock solution.…”
Section: Methodsmentioning
confidence: 99%
“…Symbols circled by a dotted line indicate significant differences (P Ͻ 0.002) compared to the control (no fatty acid) at the particular polymyxin B concentration. molecules, such as fatty acids, often serve as signals for chemotaxis and quorum sensing (41,42). Furthermore, the effects of fatty acids on bacterial motility have been documented (30,43).…”
Section: Figmentioning
confidence: 99%